Structural analysis of mouse rDNA: coincidence between nuclease hypersensitive sites, DNA curvature and regulatory elements in the intergenic spacer. - Längst, G (1997)
We have analyzed the chromatin structure of mouse ribosomal RNA genes (rDNA) by partial digestion of genomic DNA with micrococcal nuclease (MNase), DNase I and identified hypersensitive sites by indirect end-labeling. This analysis has revealed defined regions of nuclease hypersensitivity in the intergenic spacer which in turn coincide with regulatory elements. Hypersensitive sites map to the transcription initiation site, the enhancer repeats, the spacer promoter and two sequence elements which coincide with amplification-promoting sequences. Analysis of the DNA curvature by computer modeling uncovered a striking correlation between sequence-directed structural features of regulatory regions and the position of nuclease hypersensitive sites. Moreover, we demonstrate that nucleosomes are specifically positioned upstream and downstream of the transcription start site. In vitro studies using chromatin assembled in the presence of Drosophila embryo extracts show that binding of the transcription termination factor TTF-I to the upstream terminator mediates this specific nucleosome positioning at the rDNA promoter in an ATP- dependent fashion.